Buckling behaviour of Q460GJ welded H-section columns subjected to minor axis under axial compression. (December 2021) - Deng, Yanzhi; Zhou, Shurong; Li, Jingyao; Nie, Shidong; Liu, Peng
Abstract: To study the overall buckling behavior of Q460GJ steel columns around the minor principal axis under axial compression, experimental investigations were carried out on 8 pin-ended H-section steel columns. The main parameter of the specimens is slenderness λ, ranging from 36 to 86. Besides, material properties, initial geometrical imperfections and residual stresses of the specimens were measured. During the loading process, horizontal displacements at the mid-span of the specimens and the strain development were monitored. All the specimens failed with overall buckling and the bearing capacity was obtained. Moreover, a finite element model that considered initial geometric imperfections and residual stress was established and verified, and numerical studies were followed. The buckling factor φ - nondimensional slenderness λ n relationship is compared with that in current design specifications. The curve "c" in the Chinese standard GB50017-2017 and curve "c" in Eurocode 3 are recommended to evaluate the overall buckling resistance of 460GJ welded H-section columns under axial compression conservatively.